Hydroxy-Safflower Yellow A Alleviates Osteoporosis in Ovariectomized Rat Model by Inhibiting Carbonic Anhydrase 2 Activity - Yang Wang (Frontiers Media S.A., 2021)
Background: To investigate the therapeutic effect of Hydroxy-safflower yellow A (HSYA) on rat’s osteoporosis and explore its potential mechanism of action.Methods: Bilateral ovariectomized female rats (OVX) were used to establish a postmenopausal rat model of osteoporosis. HSYA was given as an intervention, and estradiol was used as a positive control. The levels of serum alkaline phosphatase (ALP), calcium ion (Ca2+), and inorganic phosphorus (IP) were used to detect bone loss. Three months after modeling, the rats were sacrificed and the rat’s ovaries, kidneys, tibia, and femur were used to calculate the organ index. The bone marrow of the femur of the rats was stained with Giemsa staining. The femur strength of rats was measured by INSTRON. The degree of osteoporosis was detected by pathological staining after decalcification of bone tissue. Predicted the main targets of HSYA in combination with bioinformatics, and the proteins related to osteoclast differentiation were detected in combination with western blotting. The effect of HSYA on the differentiation of RAW264.7 cells into osteoclasts was observed.Results: The Giemsa staining and serum test results showed that the operation was successful and affected bone metabolism. In the bone strength test, HSYA significantly increased the maximum threshold of femoral load in rats. Pathological examination showed that tibial cartilage, trabecular bone, and cortex significantly increased after treatment with HYSA. The number of osteoblasts increased while the number of osteoclasts decreased—elevated levels of type I and III collagen. Autodock was used for molecular docking of potential targets of HSYA. qPCR and western blot were used to show that the expression levels of CA2 and osteoclast differentiation-related proteins were significantly decreased after HSYA treatment. Cell level results showed that HSYA could inhibit the activity of osteoclasts and the ability of RAW264.7 cells to differentiate into osteoclasts.Conclusion: HSYA can inhibit the differentiation and formation of osteoclasts by inhibiting the expression of CA2 and relieving osteoporosis symptoms in OVX rats.